A Crisis of Banks as Liquidity Providers - ACHARYA, VIRAL V.; MORA, NADA (Journal of Finance, 2015)
ABSTRACT Can banks maintain their advantage as liquidity providers when exposed to a financial crisis? While banks honored credit lines drawn by firms during the 2007 to 2009 crisis, this liquidity provision was only possible because of explicit, large support from the government and government‐sponsored agencies. At the onset of the crisis, aggregate deposit inflows into banks weakened and their loan‐to‐deposit shortfalls widened. These patterns were pronounced at banks with greater undrawn commitments. Such banks sought to attract deposits by offering higher rates, but the resulting private funding was insufficient to cover shortfalls and they reduced new credit.